A prática tradutória na formação docente inicial em língua espanhola: uma ferramenta para a conscientização da interlíngua e do nível de proficiência linguístico e cultural dos licenciandos - Andrade, Daniele Wulff de (2018)
This research focuses on the use of translation as a pedagogic tool for initial additional language teaching training. It was presupposed that translation practice is a methodological alternative which is able to become students aware of the linguistic and cultural dimension implied on the process of learning an idiom. Such understanding results on a major monitoring of students’ written production and of the influence of Portuguese Language on their usage of Spanish Language. In such context, the comprehension of the use of translation as a pedagogical tool on the teaching of Spanish as a additional language field demands teachers and students overcoming and deconstructing two myths: think that teaching languages can be done in a limited and non contextualized way that except cultural issues and the believe that the additional language is homogenous or with few isolated variants. On the base of Applied Linguistics, Contrastive Linguistics and Functionalist Translation Theory, the research developed had the aim of verify to which extend translation practices along with the teaching of the cultural component of Spanish language and the linguistics differences among Portuguese and Spanish languages contributes to the teaching of Spanish language for training language teachers purposes at the first year of the Undergraduate Program of Portuguese and Spanish Linguistics and Literature of Unioeste campus of Marechal Cândido Rondon. To pursuit it´s aim, the following previous researches were used: Durão (2004); Durão; Durão; Seide (2016); Ferrarezi Junior (2008); Laiño (2014); Leffa (2008); Alves; Magalhães; Pagano (2015), Tessaro (2012) and Petrulionė (2012). According to qualitative and quantitative research paradigms, data was generated by interview to first year students and all the Spanish languages lecturer´s of the program, pedagogic intervention and application of two translation practices activities. Results of this case study showed that the use of translation practices has a positive influence on initial teacher language training as they are effective to make students perceive their own progress of Spanish as additional language not only on it´s linguistics aspects but also on its cultural aspects